2003
DOI: 10.1046/j.1523-1755.2003.00726.x
|View full text |Cite
|
Sign up to set email alerts
|

Hypercholesterolemia is a prerequisite for puromycin inducible damage in mouse kidney

Abstract: Hypercholesterolemia, possibly via LPO, is a prerequisite for puromycin-inducible glomerular damage in the mouse. Furthermore, nephrin protein and mRNA levels appear to be candidate markers of glomerular damage in the mouse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 40 publications
(8 reference statements)
1
19
0
Order By: Relevance
“…As previously described [12,13], injection of 150 mg/kg PAN could not induce either proteinuria or any other serum abnormalities of nephrotic syndrome in these mice (data not shown). On the other hand, a higher dosage of PAN (450 mg/kg) did induce proteinuria in all of the tested mouse strains, as shown in figure 2.…”
Section: Resultssupporting
confidence: 79%
“…As previously described [12,13], injection of 150 mg/kg PAN could not induce either proteinuria or any other serum abnormalities of nephrotic syndrome in these mice (data not shown). On the other hand, a higher dosage of PAN (450 mg/kg) did induce proteinuria in all of the tested mouse strains, as shown in figure 2.…”
Section: Resultssupporting
confidence: 79%
“…We used male mice because female mice are relatively resistant. Previous studies successfully induced PAN nephrosis in mice after a high dosage (500 mg/kg subcutaneously), 34 after a high-cholesterol diet, 35 or with multiple doses (20 mg/kg subcutaneously or 90 mg/kg intraperitoneally). 36,37 We found that PAN led to an increase in UAE associated with foot process effacement and a reduction in podocin and ZO-1 mRNA expression.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, PA studies utilize male Sprague-Dawley rats weighing between 90 and 200 g. Despite slight differences in quantity and onset, proteinuria and ultrastructural changes are reproducible among many different rat strains. Although there are a few exceptions, historically mice have been resistant to PAN (29,41,120).…”
Section: Rat Model Of Puromycin Aminonucleoside Nephrosismentioning
confidence: 99%